Fluorescence studies of 2-quinolinones and coumarins including peptide derivatives in solution and in lipid membranes - Abreu, Ana S. (2012)
Photophysical properties of 2-quinolinones and coumarins, including peptide derivatives, were determined. Fluorescence emission and anisotropy measurements of compounds incorporated in lipid vesicles were performed. Our studies indicate that these compounds may be used as fluorescent probes for peptides and lipid membranes.